PETROLEUM GENERATION POTENTIALS OF THE UPPER CRETACEOUS DUKUL AND NUMANHA FORMATIONS OF THE YOLA SUB – BASIN, UPPER BENUE TROUGH, NORTHEASTERN NIGERIA - Isiaka, Mamuda; Paul Meshach, Akushai, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2024)
Nigeria’s current petroleum and gas reserves are put at 35 billion barrels and 170 Trillion standard cubic feet (TCF) respectively. The above figures call for caution and the need for continuous and more aggressive exploration strategy to find more oil fields if the nation will continue to rely on crude oil exportation as one of its foreign earnings. The research is aimed at determining the Petroleum Generation Potential of rock samples from the Upper Cretaceous Dukul and Numanha Formations in Yola Sub-Basin using Geochemical Analysis where the organic matter quality (Type), quantity (Richness), thermal maturity and the hydrocarbon generation potentials will be determined. Also the research work in aim at determining the influence of localized volcanic activity on the rock samples maturity and its relationship to hydrocarbon generation using temperature at maximum (Tmax). The total organic carbon (TOC) content were determined to be generally low in all the samples analysed (0.25 wt %) – 0.65 wt %). The rock samples are classified as being fair to relatively good source rocks for petroleum generation. The kerogen type was observed to be predominantly Type III and IV indicating the rock samples are rich in gas with limited quantity of liquid hydrocarbon. Vitrinite reflectance (Ro) and pyrolysis data (Tmax) showed that the samples analysed have entered oil window to post matured stage. High thermal maturities of the samples clearly indicate that the localized volcanic activity has influenced the nature of the organic matter thereby cracking the organic matter into thermogenic gas within the sub-basin.